2018
DOI: 10.24990/injec.v2i2.159
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiviness of Mini-Cex Towards Clinical Competency Achievement in Neurological Examination of Clinical Practice Nursing Students

Abstract: Introduction: Mini-CEX (Mini Clinical Evaluation Exercise) is a method of evaluation to assess the clinical skills of students through direct observation and provide constructive feedback. The aim of this study was to evaluate the effectiveness of Mini-CEX towards clinical competency achievement in neurological examination of clinical practice nursing students at General Hospital Medan.Methods: The research design was quasi experiment with the post-test only with control group approach. The samples were 60 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…In the studies that have been done so far, the researchers have concluded that the mini-CEX approach improves clinical competency. The study by Amila et al, which was conducted on nursing students with the aim of investigating the impact of mini-CEX in achieving clinical competency in clinical examinations, reported an improved clinical competency among nursing students through the use of mini-CESX evaluation approach (Amila et al, 2018). Another study was conducted by Jasemi et al to investigate the impact of evaluations made by the direct observation of procedural skills (DOPS) and the traditional portfolio method on learning clinical skills among nursing students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the studies that have been done so far, the researchers have concluded that the mini-CEX approach improves clinical competency. The study by Amila et al, which was conducted on nursing students with the aim of investigating the impact of mini-CEX in achieving clinical competency in clinical examinations, reported an improved clinical competency among nursing students through the use of mini-CESX evaluation approach (Amila et al, 2018). Another study was conducted by Jasemi et al to investigate the impact of evaluations made by the direct observation of procedural skills (DOPS) and the traditional portfolio method on learning clinical skills among nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical competency consists of integrated capabilities and abilities in the eld of knowledge, attitude and skills that is a prerequisite for nursing practice and includes problem solving skills and the ability to function effectively, which in some specialties, such as nursing, is a requirement to ful ll the job role and maintain the professional position (Sultana, 2009). The lack of clinical competency causes the student to be incompetent in treating patients, performing nursing procedures and performing other hospital duties (Amila, Hasibuan, & Sinurat, 2018). Studies have shown that students new to nursing traineeship, do not have the adequate skills and pro ciency in clinical settings, despite having a strong theoretical knowledge, and act poorly in the problem-solving process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most much of the time utilized appraisal devices that action the learners' exhibition in working environment is the mini-Clinical Evaluation Exercise (mini-CEX). In its unique structure, the mini-CEX is a 9-point rating scale coordinated in three degrees of inadmissible (1)(2)(3), acceptable (4)(5)(6), and high good (7)(8)(9). A specialist, generally an employee, notices the real presentation of residents, rates their set of experiences taking and actual assessment abilities, and gives input to them.…”
Section: Mini-cexmentioning
confidence: 99%
“…Clinical competency consists of integrated capabilities and abilities in the field of knowledge, attitude and skills that is a prerequisite for nursing practice and includes problem solving skills and the ability to function effectively, which in some specialties, such as nursing, is a requirement to fulfill the job role and maintain the professional position [ 4 ]. The lack of clinical competency causes the student to be incompetent in Patient education, performing nursing procedures and performing other hospital duties [ 5 ]. Studies have shown that students new to nursing traineeship, do not have the adequate skills and proficiency in clinical settings, despite having a strong theoretical knowledge, and act poorly in the problem-solving process.…”
Section: Introductionmentioning
confidence: 99%